2001
DOI: 10.1054/bjoc.2001.1808
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer cells acquire competent mechanisms to escape Fas-mediated apoptosis and immune surveillance in the course of malignant transformation

Abstract: Summary Mechanisms of resistance against Fas-mediated cell killing have been reported in different malignancies. However, the biological response of immune escape mechanisms might depend on malignant transformation of cancer cells. In this study we investigated different mechanisms of immune escape in 2 well-differentiated low-grade (RT4 and RT112) and 2 poorly differentiated high-grade (T24 and TCCSUP) bladder cancer cell lines. Fas, the receptor of Fas-ligand, is expressed and shedded by human transitional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Alternatively, it could be that the association between Fas positivity and poor prognosis may be obscured by p53 mutational status. Our finding that T24 cells do not respond to Fas ligand corroborates the report of Perabo et al (29) suggesting that Fas in T24 cells is not functional. Certain patterns of Fas immunoreactivity, including cytoplasmic expression as observed in some tumors in this study, could be a manifestation of non-functional Fas (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, it could be that the association between Fas positivity and poor prognosis may be obscured by p53 mutational status. Our finding that T24 cells do not respond to Fas ligand corroborates the report of Perabo et al (29) suggesting that Fas in T24 cells is not functional. Certain patterns of Fas immunoreactivity, including cytoplasmic expression as observed in some tumors in this study, could be a manifestation of non-functional Fas (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…14,21 Furthermore, T24 cells were also found to be resistant to recombinant Fas ligand. 22 These studies in addition to others have led to the characterization of some cancer cell lines such as T24 as Fas resistant despite the presence of Fas on the cell surface with a variety of proposed mechanisms for this resistance. Prior analysis of cell death in prostate cancer cells has shown that AdGFPFasL downregulates the antiapoptotic protein c-FLIP (cellular Flice-like inhibitory protein).…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, it has been reported that FasL is expressed by poorly differentiated long-term established human bladder cancer cell lines. 24 However, no clear information is available on FasL expression by bladder TCC cells in vivo, and its relevance particularly with respect to the pathological characteristics of the tumor. 25 Moreover, little information is currently available on the functional activity of bladder TCC cell-associated FasL.…”
Section: Discussionmentioning
confidence: 99%
“…The function of tumor-expressed FasL has usually been demonstrated in vitro by the ability of tumor cell lines to induce apoptosis of either Fas-sensitive conventional target cell lines (eg, Fas-transfected P815, and Jurkat cells) or PBMCs 24,27 and TILs 28 in vitro stimulated with nonspecific stimuli (eg, PHA, and PMA-ionomycin). In agreement with these data, we show that FasL-expressing bladder TCC cells induce killing of Jurkat cells, as well as, autologous or allogeneic PHA lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%